Gender structure of Tree-of-Heaven (Ailanthus altissima (Mill.) Swingle) in the protected natural area ‘Bajfordova šuma’ on the territory of Belgrade — the basis for biological control of expansion and planned reduction - Bobinac, Martin; Šušić, Nikola; Andrašev, Siniša; Kabiljo, Milan; Gojković, Zoran (Acta herbologica, 2023)
Tree-of-Heaven (Ailanthus altissima (Mill.) Swingle) is an invasive tree species in Serbia that threatens the floristic biodiversity in natural stands in urban areas. It is a heliophyte with rapid growth in the initial phase of development and well expressed adaptability to different environmental conditions in open habitats. With early maturity and abundant fruiting almost every year, and the ability of seed to be transported far from the maternal tree, Tree-of-Heaven can colonize the stands (with disturbed stand structure) of other tree species quickly. It is a also a dioecious woody plant. If gender dimorphism of Tree-of-Heaven is used as a criterion for tree selection in thinning, it can be applied to affect the generative expansion of the species. Within the stand canopy closure, it can be used to influence the growth and survival of generative and vegetative offspring. Differentiation of fruit bearing-female and non-fruit-bearing-male flowers is carried out during the flowering on the basis of inflorescence. Selection of fruit-bearing-female flowers is carried out during the whole year by checking for presence of fruit and inflorescence petioles that are retained in the crown after the fruit shedding. Gender dimorphism of the species served as the basis of the gender structure determination in the protected natural area ,,Bajfordova šuma” in Belgrade.Out of 40.08 ha of the protected natural area, Tree-of-Heaven was recorded individually or in groups in the area of 27.09 ha, with 131 sexually differentiated trees with diameters within the range of 5–74 cm and heights within the range of 5–21 m.Within the beforementioned number of trees, the share of female and male trees is almost equal, but varies spatially. The recorded female and male trees are the basis for monitoring, planned reduction and Tree-of-Heaven growing in an non-invasive form in the protected natural area ,,Bajfordova šuma”.
Keywords: invasive neophytes, urban forests, qunatitive representation, thinning